Procyanidin B2 Protects Aged Oocytes Against Meiotic Defects Through Cortical Tension Modulation - Zhuan, Qingrui; Li, Jun; Zhou, Guizhen; Du, Xingzhu; Liu, Hongyu; Hou, Yunpeng; Wan, Pengcheng; Fu, Xiangwei (Frontiers in Veterinary Science, 2022)
Defects in meiotic process are the main factors responsible for the decreased developmental competence in aged oocytes. Our recent research indicated that natural antioxidant procyanidin B2 (PCB2) promoted maturation progress in oocytes from diabetic mice. However, the effect of PCB2 on aging-induced chromosome abnormalities and the underlying mechanism have not been explored. Here, we found that PCB2 recovered aging-caused developmental arrest during meiotic maturation, germinal vesicle breakdown (GVBD) rate was significantly higher in aged oocytes treated with PCB2 (P<0.05). Furthermore, we discovered that cortical mechanics were altered during aging process, cortical tension-related proteins were aberrantly expressed in aged oocytes (P<0.01). PCB2 supplementation efficaciously antagonized aging-induced decreased cortical tension (P<0.01). Moreover, PCB2 restored spindle morphology (P<0.01), maintained proper chromosome alignment (P<0.05), and dramatically reduced reactive oxygen species (ROS) level (P<0.05) in aged oocytes. Collectively, our results reveal that PCB2 supplementation is a feasible approach to protect oocytes from reproductive aging, contributing to the improvement of oocytes quality.